Pengaturan dan Perlindungan Hukum bagi Konsumen atas Penjualan Parfum Tanpa Izin Edar - Miktam, Zefanya; Kurniawan, Shelly (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Refillable perfumes, commonly known as perfumes without distribution permits, differ from official refills provided by well-known brands such as LV, Dior, or Hermès. In practice, perfumes without distribution permits do not yet have full permits from the BPOM (Indonesian Food and Drug Authority), as permits are only granted for perfume essences. The blending process, which takes place directly in front of consumers, creates uncertainty, as consumers are unaware of the additional ingredients used by the seller. These blended products should be sent to the BPOM to obtain an official distribution permit, so that the composition, including the methanol content, can be stated in detail. This study aims to analyze the legality of perfumes without distribution permits from the perspective of health law and consumer protection. The method used is a normative juridical approach with a statutory and conceptual approach. The results indicate that refillable perfumes are classified as products without distribution permits because the blending process is not supervised by the BPOM. The main problem is the weak oversight of additional ingredients, including the potential use of methanol, which is harmful to health. The growing stigma that perfumes without a marketing authorization are better used on clothing stems from consumer experiences of skin irritation or burning. The implications of this research emphasize the importance of restricting or even banning the use of methanol in perfumes without a marketing authorization, given its long-term impact on public health. The authors recommend that Indonesia follow the example of European countries that have declared methanol an illegal ingredient in cosmetics. Therefore, this research serves to strengthen BPOM regulations and provide greater protection under health and consumer law, leading to better legal standards for the supervision of perfume products in Indonesia.